Correlation between Floor Space and Sanitation of Cage with Mastitis Disease Occurrence on The Dairy C - Hastuti, S (ANIMAL PRODUCTION, 2000)
The objective of research was to know the correlation between floor space and sanitation of cage with mastitis disease occurance on the dairy cattle. Sixtiy infected mastitis disease dairy cows were used in the research in the Banyumas regency. Survey was applied in this experiment and Linier Multiple Regression was used. The result showed that there were correlations between floor spaceÂ  and sanitation of cage with mastitis which follow the regression line Yi = 15,355 + 1,087 X1 â 0,249 X2 (Animal Production 2(1): 9-12Key Words: mastitis, floor space, and sanitation